2020
DOI: 10.1109/access.2020.2999059
|View full text |Cite
|
Sign up to set email alerts
|

A Spatio-Temporal Hierarchical Model for Crowd Formation Planning in Large-Scale Performance

Abstract: Crowd formation of aesthetic transformation is considered to have extremely high artistic value and is widely applied in large-scale performances. In this paper, a spatio-temporal hierarchical model that parts the crowd formation transform into multiple granularities is proposed. Its core idea is to add spatio-temporal constraints created by directors into transformation process after multi-level division. In this model, average hash value and energy optimization are used to achieve reasonable crowd formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…In addition to the global moving distance, researchers have proposed a number of indicators to measure crowd formations, such as stability of the local structure, 1 effort balancing 1 and fitness of appearance to the director's intention. 3 However, after interviews with several international directors, we concluded that artistic aesthetics are not entirely objective and cannot be qualitatively measured through metrics. This does not mean that metrics are completely meaningless.…”
Section: Effectiveness Metricsmentioning
confidence: 94%
See 4 more Smart Citations
“…In addition to the global moving distance, researchers have proposed a number of indicators to measure crowd formations, such as stability of the local structure, 1 effort balancing 1 and fitness of appearance to the director's intention. 3 However, after interviews with several international directors, we concluded that artistic aesthetics are not entirely objective and cannot be qualitatively measured through metrics. This does not mean that metrics are completely meaningless.…”
Section: Effectiveness Metricsmentioning
confidence: 94%
“…Crowd formation transformation can be described as a series of processes that transform between crowd formations. The crowd formation can be expressed as a set of agents 3 , or other linear space. Moving from one crowd formation to another is called a transformation:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations